Faktor-Faktor yang Berpengaruh terhadap Penentuan Materialitas dalam Audit Laporan Keuangan - Galuh Artika Febriyanti (JIATAX (Journal of Islamic Accounting and Tax), 2018)
The aim of this research to examine empirically whether independence auditor, professionalism, auditor’s experience, audit structure, audit quality, and audit risk partially dan simultaneously influence towards materiality determination on audit financial statements. Research method used to examine hypotheses uses simple regression analysis to partially examine the effect of independence auditor, professionalism, auditor’s experience, audit structure, audit quality, and audit risk towards materiality determination on audit financial statements. Multiple regression analysis also used to examine simultaneously the effect of independence auditor, professionalism, auditor’s experience, audit structure, audit quality, and audit risk towards materiality determination on audit financial statements. The results showed partially independence auditor, professionalism, auditor’s experience has not effect towards materiality determination on audit financial statements. The results also showed partially auditor’s experience, audit structure, audit quality, and audit risk effect towards materiality determination on audit financial statements. Simultaneously examination showed independence auditor, professionalism, auditor’s experience, audit structure, audit quality, and audit risk affect towards materiality determination on audit financial statements.